Firm foundations: The statistical footprint of multinational corporations as a problem for political economy - Timur Ergen; Sebastian Kohl; Benjamin Braun (Max Planck Institute for the Study of Societies, 2021)
The discipline of comparative political economy (CPE) relies heavily on aggregate, country-level economic indicators. However, the practices of multinational corporations have increasingly undermined this approach to measurement. The problem of indicator drift is well-documented by a growing critical literature and calls for systematic methodological attention in CPE. We present the case for a rocky but ultimately rewarding middle road between indicator fatalism and indicator faith. We illustrate our argument by examining two important cases - Sweden's recent export success and the financialization of non-financial corporations in France. A careful parsing of the data suggests corrections to common characterizations of the two cases. Swedish exports have been reshaped by intragroup trade among foreign subsidiaries of domestic corporations. The growth of financial assets held by French firms is attributable to the growth of foreign direct investment and to cumulative revaluation effects, while what remains of financialization is concentrated among the very largest firms. Based on these findings, we propose a methodological routine that parses data by zooming in on the qualitative specifics of countries, sectors, and firms, while using all available options for disaggregation. – – Die vergleichende politische Ökonomie (CPE) stützt sich in hohem Maße auf aggregierte, ländervergleichende Wirtschaftsindikatoren. Die Praktiken multinationaler Unternehmen haben diesen Ansatz jedoch zunehmend unterminiert. Das Problem abdriftender Indikatoren wird durch eine wachsende kritische Literatur gut dokumentiert und erfordert eine systematische methodische Antwort. Wir plädieren für einen Mittelweg zwischen Indikator-Fatalismus und Indikator-Glauben und veranschaulichen unser Argument anhand von zwei wichtigen Fällen - Schwedens jüngstem Exporterfolg und der Finanzialisierung von nichtfinanziellen Unternehmen in Frankreich. Eine sorgfältige Analyse der Daten zeigt, dass der Handel zwischen ausländischen Tochtergesellschaften inländischer Unternehmen die schwedische Exportstatistik prägt und dass das Wachstum der von französischen Unternehmen gehaltenen Finanzaktiva auf ausländische Direktinvestitionen und kumulative Bewertungseffekte zurückzuführen und außerdem auf multinationale Großunternehmen konzentriert ist. Methodisch schlagen wir die routinemäßige Rückbindung vergleichender Analysen an die qualitativen Besonderheiten von Ländern, Sektoren und Unternehmen vor sowie eine verstärkte Nutzung verfügbarer Möglichkeiten zur Disaggregation.
hdl:21.11116/0000-0009-8D31-1
Keywords: 300; comparative methodology; comparative political economy; economic indicators; financialization; France; globalization; growth models; multinational corporations; Sweden; Finanzialisierung; Frankreich; Globalisierung; multinationale Unternehmen; Schweden; vergleichende Methoden; Vergleichende Politische Ökonomie; Wirtschaftsindikatoren; Wachstumsmodelle